Reformasi Peran Badan Wakaf Indonesia (BWI) dalam Ekosistem Wakaf Nasional sebagai Jalan Menuju Reforma Agraria - Ahmad Hatim (CV Rewang Rencang, 2021)
Waqf is one of the potentials that can be used as an effort towards agrarian reform. However, the fact is that waqf management has not been carried out optimally. BWI as the core institution for the development of national waqf also has problems in the division of roles in it. The problem of the role is the Indonesian Waqf Agency which acts as a regulator and operator as stated in article 49 of the Waqf Act turns out to cause conflicts of interest. Thus, the reform of the role of BWI is needed to solve existing problems so that national representation is more optimal and can be used as a path to Agrarian Reform so that it can be accessed by anyone and provide the widest benefits for the people.